Moving toward a true depiction of tobacco behavior among Asian Indians in California: Prevalence and factors associated with cultural smokeless tobacco product use - Mukherjea, Arnab; Modayil, Mary V.; Tong, Elisa K. (Cancer, 2018)
BACKGROUND Asian Indians (AIs) in the United States exhibit disproportionate burdens of oral cancer and cardiovascular disease, which are potentially linked to smokeless tobacco. However, little is known about the use of cultural smokeless tobacco (CST) products in this population. METHODS California Asian Indian Tobacco Use Survey data from 2004 (n = 1618) were used to investigate CST prevalence among California's AIs. CST products included paan, paan masala, and gutka. A multivariable logistic regression was conducted to examine factors (socioeconomic status, acculturation measures, and religious affiliation) associated with current CST use versus never use. RESULTS The current CST prevalence was 13.0% (14.0% for men and 11.8% for women). In contrast, the prevalence of current cigarette use was 5.5% (8.7% for men and 1.9% for women), and the prevalence was lower for cultural smoked tobacco (0.1% for bidis and 0.5% for hookahs). Factors associated with CST use included the following: being male, being 50 years old or older, being an immigrant, speaking an AI language at home, having a higher level of education (adjusted odds ratio [AOR] for high school/some college, 2.6; 95% confidence interval [CI], 1.1‐6.5; AOR for college degree or higher, 4.0; 95% CI, 1.7‐9.5), having a higher income (AOR for $75,000‐$100,000, 2.5; 95% CI, 1.3‐4.7; AOR for ≥$100,000, 2.6; 95% CI, 1.4‐5.0), identifying as non‐Sikh (AOR for Hinduism, 10.0; 95% CI, 6.0‐16.5; AOR for other faiths, 10.2; 95% CI, 5.9‐17.7), and disagreeing that spiritual beliefs are the foundation of life (AOR, 2.1; 95% CI, 1.2‐3.5). CONCLUSIONS The current CST prevalence is relatively high among California's AIs in comparison with the prevalence of smoking, with narrower differences between sexes. The association with a higher socioeconomic status is contrary to typical cigarette smoking patterns. Acculturation and religious affiliation are important factors associated with current use. Health care providers and policymakers should consider such determinants for targeted interventions. Cancer 2018;124:1607‐13. © 2018 American Cancer Society. A unique population‐based statewide survey (the California Asian Indian Tobacco Use Survey) has been used to investigate the prevalence and correlates of cultural smokeless tobacco products (paan, paan masala, and gutka) in California's rapidly growing Asian Indian population. The results indicate a considerably higher prevalence of cultural smokeless tobacco, in comparison with cigarette use, among both men and women and an association with a higher socioeconomic status.